Comparison of Phosphonium and Sulfoxonium Ylides in Ru(II)-Catalyzed Dehydrogenative Annulations: A Density Functional Theory Study - Wei Zhou; Lei Zhang; Dan-Yang Liu; Xiaosi Ma; Jie Zhang; Jiajia Kang (Molecules)
Density functional theory calculations have been performed to explore the detailed mechanism of a ruthenium-catalyzed dehydrogenative annulation between α-carbonyl phosphonium ylide (A) and sulfoxonium ylide (B). The proposed catalytic cycles consist of several elementary steps in succession, namely the C–H activation of ylide A, the insertion of ylide B, reductive elimination, protodemetallation, and an intramolecular Wittig reaction, in which C–H activation is rate-limiting, with a free energy barrier of 31.7 kcal/mol. As A and B are both capable of being a C–H activation substrate and a carbene precursor, there are potentially four competing pathways including homo-coupling reactions. Further calculations demonstrate that A is more reactive in the C–H activation step than B, while the opposite conclusion is true for the ylide insertion step, which can successfully explain the fact that the solely observed product originated from the use of A as the C–H activation substrate and B as the carbene precursor. Molecular electrostatic potential, charge decomposition, and electron density difference analyses were performed to understand the distinct behaviors of the two ylides and the nature of the key ruthenium–carbene intermediate.